Methods for estimating the amount of slag in the cohesive zone of a blast furnace and methods for its operation

JP7644352B2Active Publication Date: 2025-03-12NIPPON STEEL CORPORATION
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021122562
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-27
Publication Date
2025-03-12
Estimated Expiration
2041-07-27

AI Technical Summary

Benefits of technology

【0024】 本発明によれば、焼結鉱、ペレット、塊鉱石などの鉄含有装入物を配合して装入する高炉操業において、融着帯の融液量を推定できる。その結果、高炉炉下部の炉況、特に、通気性の適否を正確に評価することが可能となる。また、高炉操業管理指標の一つとして融着帯スラグ量を用いることで、高炉炉下部における温度低下を抑制して、操業を安定化することができる。さらに、還元材比を低減して、省エネルギー化、低CO2化も期待できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644352000004
    Figure 0007644352000004
  • Figure 0007644352000005
    Figure 0007644352000005
  • Figure 0007644352000006
    Figure 0007644352000006
Patent Text Reader

Abstract

To accurately calculate an amount of slag present in a cohesive zone (cohesive zone slag amount) formed by melting iron-containing charging materials and to properly evaluate furnace conditions in a blast furnace operation in which several kinds of iron-containing charging materials, such as sintered ore, pellets and lump ore, are usually mixed and charged at an arbitrary blending ratio.SOLUTION: Provided is a method for evaluating furnace conditions in a blast furnace operation in which iron-containing charging materials and carbonaceous charging materials are alternately charged into a blast furnace and the iron-containing charging materials are heated and reduced to produce pig iron. The method includes: (i) defining a cohesive zone slag amount present in a cohesive zone formed by melting of the iron-containing charging materials: CSV (kg / tp) by the following formula; and (ii) evaluating the furnace conditions in a lower part of the blast furnace using the cohesive zone slag amount (kg / tp) as an index. CSV (kg / tp)=remaining FeO amount (kg / tp)+gangue amount (kg / tp)SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for estimating the amount of cohesive zone slag, which is an index that accurately represents the furnace condition in the lower part of a blast furnace, and a method for operating a blast furnace using the index. [Background technology]

[0002] Conventionally, sinter, pellets, lump ore, etc. have been used as iron-containing charges in blast furnace operation. In order to stabilize blast furnace operation, the particle size distribution, cold strength, reduction characteristics, etc. of these charges have been improved, and the amount of self-fluxed sinter with good properties has been increased. In particular, since the reducibility of the iron-containing charges affects reaction efficiency, aeration stability, thermal stability, etc., improvements and optimization of these influencing factors have been earnestly pursued.

[0003] For example, Patent Document 1 discloses that in blast furnace operation with a pulverized coal injection rate of 150 kg / tp (injection rate per ton of pig iron. " / tp" means per ton of pig iron) or more, the proportion of high alumina sintered ore containing SiO2: 3.9-4.9 mass%, MgO: 0.5-less than 1.2 mass%, Al2O3: 1.8-2.5 mass%, CaO / SiO2 (mass ratio): 1.9-2.5 is 50-80 mass% of the charge, and a large amount of high alumina sintered ore is used and the amount of blast furnace slag is reduced. According to the blast furnace operation of Patent Document 1, it is possible to reduce the slag ratio to 290 kg / tp or less.

[0004] The slag ratio (amount of slag) means the amount of slag generated per ton of pig iron. Slag is composed of gangue components (CaO, SiO2, Al2O3, MgO) other than iron and carbon contained in the blast furnace charge and the injected pulverized coal, and the amount is approximately 250 to 320 kg / tp. The slag ratio (amount) is one of the controlling factors that govern the permeability of the lower part of the blast furnace.

[0005] Patent Document 2 discloses that in blast furnace operation with a pulverized coal injection rate of 170 kg / tp or more, sintered ore (SiO2: 4.0-4.6 mass%, MgO: 1.0-1.4 mass%, FeO: 4.0-7.0 mass%, basicity (CaO / SiO2) (mass ratio): 2.0-2.3) with a reduction disintegration index RDI of 40% or more is used. According to the blast furnace operation of Patent Document 2, it is possible to reduce the slag rate to 280 kg / tp or less.

[0006] However, the slag ratio (amount) described in Patent Documents 1 and 2 is the ratio (amount) of the discharged slag after the reduction is completed, and does not accurately indicate the amount of the molten liquid (which also contains unreduced FeO) generated in the blast furnace in an unreduced state.

[0007] The actual amount of molten liquid in a blast furnace, especially in the cohesive zone, depends heavily on the permeability of the blast furnace. Even if the composition of the charge is designed to reduce the slag ratio, the amount of molten liquid in the cohesive zone may increase if the charge has poor reducibility. For this reason, in blast furnace operation, the slag ratio (amount) and the furnace permeability index often do not match. Therefore, it is necessary to find a precise index that can accurately indicate the permeability inside the blast furnace and manage the operation.

[0008] In a blast furnace, several kinds of iron-containing charges, such as sintered ore, pellets, lump ore, are usually mixed at an arbitrary mixing ratio. It has been proposed to collectively index these as the characteristics of the blast furnace charge and to manage the blast furnace operation.

[0009] Patent Document 3 discloses a method for managing the high-temperature properties of sintered ore, which is characterized by calculating the permeability index at the high-temperature part of sintered ore using a formula, estimating the high-temperature properties of sintered ore from the calculated value, and managing them. According to the method of Patent Document 3, the high-temperature properties of sintered ore can be estimated from commonly used management indices such as RDI (reduction disintegration index) and RI (reducibility), enabling rapid burden mix design. However, the method of Patent Document 3 is applicable only to sintered ore and cannot be applied to the mix design of burdens including other burdens.

[0010] Patent Document 4 discloses a method for adjusting the blending of iron-containing raw materials to be charged into a blast furnace, which is characterized by blending the iron-containing raw materials to be charged into a blast furnace so that the weighted average air permeability index for high-temperature properties at 1000°C or higher of the iron-containing raw materials to be charged into a blast furnace is 5.7 or less. This method makes it possible to perform stable blast furnace operation with a low Si content in molten iron.

[0011] However, although the method of Patent Document 4 is effective for selecting lump ores and for blending and adjusting, it is difficult to apply the method to all burden materials. In fact, there are cases where blast furnace operation deteriorates even when the average air permeability index of the burden material is 5.7 or less.

[0012] In measuring the high-temperature properties of a charging material, the air permeability resistance index is significantly affected by the packing structure (void ratio, etc.), so taking a weighted average of the air permeability resistance index of a single brand does not take into account the change in the packing structure that occurs when several charging materials are mixed and charged. Therefore, the method of Patent Document 4 has the problem that the range of application is limited. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] Japanese Patent Application Publication No. 11-43710 [Patent Document 2] JP 2002-256312 A [Patent Document 3] Japanese Patent Application Publication No. 60-89525 [Patent Document 4] Japanese Patent Publication No. 59-38308 Summary of the Invention [Problem to be solved by the invention]

[0014] In blast furnace operation, in which several types of iron-containing charges, such as sintered ore, pellets, and lump ore, are usually mixed and charged at an arbitrary mixing ratio, no index has been proposed to evaluate the furnace condition, particularly the quality of gas permeability. In blast furnace operation, the quality of gas permeability in the furnace depends on the amount of molten liquid (amount of slag) present in the cohesive zone formed by melting the iron-containing charges, but even if the slag components of the entire blast furnace charge are grasped comprehensively, the amount of molten liquid (amount of slag) present in the cohesive zone cannot be accurately predicted.

[0015] Therefore, an object of the present invention is to provide a method for accurately estimating the amount of molten liquid present in a cohesive zone formed by melting an iron-containing charge in a blast furnace operation in which several types of iron-containing charge, such as sintered ore, pellets, and lump ore, are usually mixed and charged at an arbitrary mixing ratio, and to provide a blast furnace operation method utilizing the estimated value.

[0016] Hereinafter, the amount of molten liquid present at the upper surface portion of the cohesive zone will be referred to as the "cohesive zone slag amount" and abbreviated as "CSV". [Means for solving the problem]

[0017] The present inventors have intensively studied a method for solving the above problems. As a result, they have found that the amount of slag in the cohesive zone, which is the amount of molten liquid present on the upper surface of the cohesive zone of a blast furnace, can be estimated by the formula (1), and that the furnace condition in the lower part of a blast furnace, in particular, the adequacy of gas permeability, can be appropriately evaluated using the amount of slag in the cohesive zone as an indicator. Amount of slag in the cohesive zone = Amount of FeO remaining on the upper surface of the cohesive zone + Amount of gangue in the iron-containing burden (1) The present invention has been made based on the above findings, and the gist of the present invention is as follows.

[0018] According to one aspect of the present invention, in blast furnace operation in which an iron-containing charge and a carbonaceous charge are alternately charged into a blast furnace and the iron-containing charge is heated and reduced to produce pig iron, a method for estimating the amount of cohesive zone slag: CSV (kg / tp), which is the amount of molten liquid present on the upper surface of the cohesive zone formed by melting the iron-containing charge, is provided, the method being characterized by estimating the amount of cohesive zone slag: CSV (kg / tp) as the sum of the amount of FeO remaining on the upper surface of the cohesive zone of the iron-containing charge (kg / tp) and the amount of gangue of the iron-containing charge (kg / tp).

[0019] Here, a load-softening test may be performed on the iron-containing charge to determine the reduction rate Rs of the iron-containing charge at the time when the pressure drop starts to increase, and the amount of remaining FeO (kg / tp) may be calculated by the following formula (Ix). Residual FeO amount (kg / tp) = (1833.236-202.842×FeO[%] / T.Fe[%])×(1-Rs / 100) (Ix) T.Fe: Total iron content in iron-containing charge (%) FeO: Amount of FeO in iron-containing charge (%) Rs: Reduction rate (%) at the time of pressure drop increase measured in a load-softening test for iron-containing burden

[0020] In addition, CSV of the entire burden consisting of multiple iron-containing burdens T (kg / tp) may be calculated using the following formula (II). CSV T (kg / tp)=Σ(CSV i ·w i T.Fe i ) / Σ(w i T.Fe i ) · · · (II) CSV i : Amount of slag in iron-containing charge i (kg / tp) W i : Mixture ratio (%) of iron-containing charge i, or mix unit (kg / tp) T.Fe i : T.Fe (%) of iron-containing charge i

[0021] In addition, a target value for the amount of cohesive zone slag may be set, and at least one of (a) to (d) may be performed so that the estimated value of the amount of cohesive zone slag using the above-mentioned method for estimating the amount of cohesive zone slag is equal to or less than the target value. (a) Adjustment of the mixture ratio of iron-containing materials charged to the blast furnace (b) Adjusting the content of one or more of CaO, SiO2, Al2O3, MgO, CaO / SiO2, and FeO in the iron-containing charge charged to the blast furnace. (c) Adjusting the particle size of iron-containing charge fed to the blast furnace (d) Adjusting the amount of carbonaceous burden mixed into the iron-containing burden layer

[0022] The target amount of slag in the cohesive zone may be 920 to 980 kg / tp.

[0023] The target amount of slag in the cohesive zone may be 830 to 890 kg / tp. Effect of the Invention

[0024] According to the present invention, the amount of molten liquid in the cohesive zone can be estimated in blast furnace operation in which iron-containing charges such as sintered ore, pellets, and lump ore are mixed and charged. As a result, it becomes possible to accurately evaluate the furnace conditions in the lower part of the blast furnace, in particular, the suitability of the gas permeability. In addition, by using the amount of slag in the cohesive zone as one of the blast furnace operation management indicators, it is possible to suppress the temperature drop in the lower part of the blast furnace and stabilize the operation. Furthermore, it is possible to reduce the reducing agent rate, thereby saving energy and reducing CO2. [Brief description of the drawings]

[0025] [Figure 1] The results of a heating reduction test using samples prepared by sintering sintered ore produced in a sintering machine into particles of 10 to 15 mm and the analysis results are shown in Fig. 1. (a) shows the transition of the reduction rate (%) and the change in pressure drop (mmAQ), and (b) shows the results of analyzing the heating reduction test results using the index of the present invention. [Diagram 2] FIG. 1 is a diagram showing the state of the cohesive zone and a comparison of the index of the present invention and the index of the prior art. [Diagram 3]The results of an analysis of the lower K value during blast furnace operation are shown. (a) shows the relationship between SV and the lower K value, and (b) shows the relationship between CSV and the lower K value. [Figure 4] This is a diagram showing that the index "CSVT" effectively functions as a management index through data analysis of blast furnace operation. The left diagram shows the relationship between the lower K value and the amount of slag in the cohesive zone (CSV), and the right diagram shows the relationship between the productivity and the amount of slag in the cohesive zone (CSV). [Diagram 5] FIG. 1 is a graph showing the particle size dependence of CSV for sintered ore and lump ore. [Figure 6] FIG. 13 is a diagram showing CSV measured by mixing a carbon-containing material with a single layer of sintered ore. [Figure 7] 1 shows the operational results of Example 1. (a) shows the operational results when evaluated using the "amount of slag in the cohesive zone" of the present invention, and (b) shows the operational results when evaluated using the conventional "amount of slag." [Figure 8] 1 shows the operational results of Example 2. (a) shows the operational results when evaluated using the "amount of slag in the cohesive zone" of the present invention, and (b) shows the operational results when evaluated using the conventional "amount of slag." DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] <Background to the invention> First, the background to the present invention will be described. (Cohesive Zone and Breathability) Iron-containing charges (sintered ore, pellets, lump ore, etc.) are charged into the top of the blast furnace. As they descend through the furnace, they are heated and reduced by reducing gases (CO, H2) produced by the reaction of hot air blown in from the tuyeres with coke, forming a cohesive zone in the blast furnace shaft. The permeability of the interior of the furnace is affected by the permeability of this cohesive zone, which in turn depends on the amount of molten liquid (amount of slag) present in the cohesive zone. (Figure 2, Diagram of the cohesive zone)

[0027] (load softening test) In order to investigate the formation behavior of the cohesive zone, a load-softening test (high-temperature property test) was conducted using a load-softening test device. The load-softening test is a test in which a packed bed in which an iron-containing charge is sandwiched between coke layers on the top and bottom is reduced in an electric furnace, and the reduction, softening, and fusion behavior of the iron-containing charge are reproduced by applying conditions to the iron-containing charge that simulate the load, temperature rise, and concentration change of the reducing gas in a blast furnace. The change in the reduction rate of the iron-containing charge is measured from the analysis of the exhaust gas, and the change in the air resistance of the packed bed is measured from the pressure change of the reducing gas passing through the packed bed. The load-softening test method was performed according to the method described in Non-Patent Document: Iron and Steel 83 (1997) 97.

[0028] (Softening behavior of sintered ore under load) Figure 1 shows the results of a load-softening test using a sample made by sintering sintered ore produced in a sintering machine to a particle size of 10 to 15 mm, and the analysis results. Figure 1(a) shows the change in reduction rate (%) and pressure drop (mmAQ). Here, the reduction rate is defined as the ratio of the amount of oxygen removed by reduction to the amount of oxygen to be reduced. Figure 1(b) shows the analysis results of the heating reduction test. The horizontal axis of Figure 1(a) and (b) is the temperature (°C) of the iron-containing charge (sintered ore in this case). The calculation method for FeO+ gangue (kg / tp) on the vertical axis of Figure 1(b) will be described later.

[0029] Figure 1(a) shows that the reduction degree increases with increasing heating temperature, and Figure 1(b) shows that the amount of molten liquid (remaining FeO + gangue) decreases with increasing reduction degree, and finally only the gangue remains. It also shows that the amount of remaining FeO is large compared to the amount of gangue, and that it is essential to take the amount of remaining FeO into account when calculating the amount of molten liquid coexisting inside the cohesive zone.

[0030] Moreover, near 1250°C, the airflow resistance rises sharply, and so does the pressure drop. This is because the gaps between the sintered ore particles that make up the sample are almost completely filled with the molten liquid (strictly speaking, molten liquid with solids suspended in it). Here, the point at which the pressure drop rises sharply (the rate at which the pressure drop rises with temperature rise is 10 (mmAQ / °C) or more) is defined as the "softening and fusion point," and the reduction degree at which the pressure drop rises sharply is defined as "Rs" (see Figure 1(a)). The softening and fusion point is essentially the threshold that distinguishes the indirect reduction zone from the smelting reduction zone, and in a blast furnace, it corresponds to the upper surface of the fusion zone (the reduction degree and temperature there).

[0031] In the heating temperature range above 1250℃, gas reduction does not proceed, and melt reduction due to contact between the molten liquid and carbon proceeds mainly. At this time, the components of the molten liquid are gangue components (CaO+SiO2+Al2O3+MgO) and unreduced FeO (wüstite phase).

[0032] Therefore, the inventors of the present invention considered that the factor governing the ventilation resistance in the lower part of a blast furnace is not the conventional amount of slag, which is the sum of CaO, SiO2, Al2O3 and MgO components in all the charges, but is essentially the temperature at which the pressure drop starts to increase, that is, the amount of molten liquid present at the upper surface of the cohesive zone. However, no means for directly measuring the amount of molten liquid or indirectly evaluating it has been proposed so far.

[0033] <Method for estimating the amount of slag in the cohesive zone> The inventors came up with the idea of ​​estimating the cohesive zone slag amount (CSV) as the sum of the amount of remaining FeO (wüstite phase) and the amount of gangue in the iron-containing burden (Equation (1)). The cohesive zone slag amount is a new index defined by the inventors in order to properly maintain the furnace conditions, particularly the furnace gas permeability, of the blast furnace, and is a fundamental feature of the present invention.

[0034] Amount of slag in the cohesive zone = Amount of FeO remaining on the upper surface of the cohesive zone + Amount of gangue in the iron-containing burden (1) FIG. 2 shows a comparison between the index proposed by the present inventors and a conventional index, and a method for estimating the amount of melt present in the cohesive zone will be described with reference to FIG.

[0035] (Amount of gangue in iron-containing burden) The amount of gangue in iron-containing burden is the total amount of components other than iron in the iron-containing burden (see Figure 2). The amount of gangue can be calculated by formula (2) using T.Fe, FeO, and Fe2O3 (mass%) as the chemical components of the burden. In the formula, "950" is the iron consumption rate (kg / tp) per ton of molten iron, determined based on the assumption that the pig iron contains 5 mass% C. In the following, "%" means "mass%". Gangue amount (kg / tp)={(100-Fe2O3[%]-FeO[%]) / T.Fe[%]}·950···(2)

[0036] Fe2O3 [%] can be calculated from T.Fe [%] and FeO [%] using formula (3).

[0037] Fe2O3[%]={(55.85×2+16×3) / 55.85×2}×{T.Fe[%]-55.85 / (55.85+16)×FeO[%]} ···(3) From equations (2) and (3), equation (4) for calculating the amount of gangue can be obtained.

[0038] Gangue amount (kg / tp)={100-{(55.85×2+16×3) / 55.85×2}×{T.Fe[%]-55.85 / (55.85+16)×FeO[%]}-FeO[%]} / T.Fe[%] ·950 =(100-1.4297×T.Fe[%]+0.1113×FeO[%]) / T.Fe[%]·950···(4)

[0039] The amount of gangue is uniquely determined from the T.Fe (mass%) and FeO (mass%) determined from chemical analysis of the burden, and is constant regardless of the progress of reduction (see "gangue" in Figure 2).

[0040] (Charge material consumption rate (ore ratio)) If the ore ratio OR (mass of iron-bearing burden (kg) / mass of pig iron (t)) is known, the gangue amount can be estimated from the chemical analysis of the iron-bearing burden using formula (5) instead of formula (4). Gangue amount (kg / tp)=OR(kg / tp) / 0.95-1000 ···(5)

[0041] (Residual FeO content) Next, the calculation of the amount of remaining FeO, which is the amount of the wustite phase remaining at the time when the pressure drop begins to increase, i.e., at the upper surface of the cohesive zone, will be described.

[0042] The reduction ratio is defined as the ratio of the amount of oxygen removed by reduction to the amount of oxygen to be reduced. Using the reduction ratio Rs at the point when the pressure drop starts to increase, we obtain Equation (6). Rs(%)={(Oi-Or) / Oi}·100···(6) From equation (6), we obtain equation (7). Or(kg / tp)=(1-Rs / 100)·Oi···(7)

[0043] Here, Oi is the amount of oxygen to be reduced (kg / tp) before reduction of the charge, and Or is the amount of remaining oxygen remaining at the reduction rate Rs (see O in the charge and O remaining during reduction in Figure 2).

[0044] Oi is calculated using equation (8). Oi(kg / tp)={16×1.5 / 55.85×{T.Fe[%]-55.85 / (55.85+16)×FeO[%]}+16 / 55.85×FeO[%]} / T.Fe[%]·950 ···(8)

[0045] Therefore, equation (9) is obtained from equation (7). Or(kg / tp)={16×1.5 / 55.85×{T.Fe[%]-55.85 / (55.85+16)×FeO[%]}+16 / 55.85×FeO[%]} / T.Fe[%]·950×(1-Rs / 100)···(9)

[0046] The amount of residual oxygen Or exists as wustite (FeO) in a furnace at 1000°C or higher, so the amount of residual FeO can be expressed by formula (10). That is, the amount of residual FeO decreases linearly as the reduction proceeds (see Figure 2).

[0047] Residual FeO amount (kg / tp)={16×1.5 / 55.85×{T.Fe[%]-55.85 / (55.85+16)×FeO[%]}+16 / 55.85×FeO[%]} / T.Fe[%]·950×(1-Rs / 100)×{(55.85+16) / 16} = (1833.236-202.842×FeO[%] / T.Fe[%])×(1-Rs / 100) ···(10)

[0048] (CSV amount of slag in the cohesive zone) From equations (4) and (10), the amount of slag in the cohesive zone can be expressed by equation (11). Amount of cohesive zone slag (kg / tp) = Amount of remaining FeO (kg / tp) + Amount of gangue (kg / tp) =(1833.236-202.842×FeO[%] / T.Fe[%])×(1-Rs / 100)+(100-1.4297×T.Fe[%]+0.1113×FeO[%]} / T.Fe[%]·950···(11)

[0049] In reality, not all of the slag in the cohesive zone is liquid at the time when the pressure drop in the furnace suddenly increases, but the slag gradually becomes liquid in the high temperature region after that point. Therefore, the indicator "cohesive zone slag volume" (CSV) newly defined by the present inventors means, precisely, the "volume of slag that can become liquid" that exists inside the cohesive zone.

[0050] (Method of determining Rs.) Rs required to estimate the amount of remaining FeO can be obtained as the reduction rate at the softening and fusion point (the point at which pressure drop begins to increase) by carrying out the above-mentioned load-softening test on the iron-containing charge.

[0051] Alternatively, the estimation may be performed by computer simulation using a mathematical model of a blast furnace.

[0052] In the load-softening test, even if the same sample is used, Rs may change depending on the reduction conditions and the characteristics of the equipment. However, since the present invention is primarily intended to relatively evaluate the suitability of the furnace conditions, it is not a problem if Rs changes.

[0053] (When the iron-containing charge consists of multiple raw materials) CSV of the entire burden, which consists of various iron-containing burden materials such as sinter, lump ore, and pellets (hereinafter referred to as "CSV") T ") can be calculated as the mass-weighted arithmetic average of the CSVs (CSVi) of the individual iron-containing charges. That is, CSV T can be calculated using equation (12).

[0054] CSV T (kg / tp)=Σ(CSV i ·w i T.Fe i ) / Σ(w i T.Fe i ) · · · (12)

[0055] Here, CSV i : CSV of charge i (kg / tp) W i : Mixture ratio of charge i (mass%) (mixture unit (kg / tp) may be used instead of the mix ratio. However, one or the other should be used for calculation.) T.Fe i : T.Fe (mass%) of charge i

[0056] Indicator “CSV T " is an index that collectively indicates the characteristics of the burden composed of various iron-containing burden materials. T " can be similarly applied to the case where a plurality of sintered ores having different characteristics are used. (Comparison with conventional indicators: CSV)

[0057] [Table 1]

[0058] Table 1 shows the total iron content (%), FeO (%), and gangue content (SV) determined by chemical analysis for various iron-containing burdens with particle sizes of 10 to 15 mm, the reduction ratio Rs (%) at the softening and fusion point measured in a load-softening test, the CSV (kg / tp) calculated using formula (11), and the S value, which is the temperature integral of the airflow resistance. Here, the total iron content of the lump ore is the value after calcination. Note that the hearth slag content (SV) used in normal operation management includes not only gangue derived from the iron-containing burden, but also auxiliary materials for adjusting the composition, coke, and ash in the pulverized coal, and is therefore about 50 kg / tp more than the gangue content derived from the iron-containing burden.

[0059] As shown in Table 1, the S value simulating the permeability inside a blast furnace does not correspond to the amount of gangue in the iron-containing burden, but corresponds well to the CSV of the present invention. This is because the CSV of the present invention takes into account not only the amount of gangue but also the amount of unreduced FeO that changes with the progress of reduction.

[0060] (Comparison with conventional indicators: CSV T ) In actual blast furnace operation, multiple iron-containing charges are mixed and used. In that case, the amount of CSV is used as the cohesive zone slag amount. T Next, SV and CSV T Here is an example comparing the above.

[0061] The change in the lower K value when 15% of sintered ore is replaced with pellets while keeping the iron production rate constant is shown in Fig. 3. The lower K value is an index for evaluating the air flow resistance in the lower part of a blast furnace and is calculated by the following formula. For a given height from the tuyere K=(P1 2 -P2 2 ) / G 1.7 Where P1: Air pressure (MPa) P2: Pressure at a specific part of the blast furnace (MPa) G: Blast furnace bosh gas volume (Nm 3 / min) In this case, the values ​​were adjusted for the coke properties, the properties of the iron-containing charge, and other operational factors. By replacing sintered ore with pellets, the hearth slag volume (SV) was reduced from 290 to 265 kg / tp, but the lower K value showed the opposite trend, worsening from 1.8 to 1.9 (Fig. 3(a)). On the other hand, the CSV, which takes into account the high-temperature reducibility of pellets, T The change at this time is shown in the average CSV of the charge. T The reduction in the permeability of the blast furnace was reasonable (Fig. 3(b)).

[0062] (Correspondence with productivity) Figure 4 shows an example of the relationship between the productivity and the amount of iron produced during one year of operation of a blast furnace where the productivity ratio changed between 1.9 and 2.2. Figure 4(a) shows the relationship between the lower K value and the amount of slag in the cohesive zone (CSV T ), and Fig. 4(b) shows the relationship between the productivity and the amount of slag in the cohesive zone (CSV T As shown in Fig. 5, the relationship between the lower K value and the amount of slag in the cohesive zone (CSV T ) and the correlation between the productivity and the amount of slag in the cohesive zone (CSV T ) is extremely good.

[0063] Based on the above, the newly defined indicator "cohesive zone slag amount", "CSV" or "CSV T It can be seen that by using “CSV” or “CSV T " is an index that directly evaluates the amount of FeO-containing melt at the upper surface of the cohesive zone. The magnitude of the index affects the thermal conditions in the lower part of the furnace, which in turn affects the reducing agent rate. It can be seen that, together with the relationship with furnace air permeability, it also shows a good correlation with the productivity.

[0064] <Blast furnace operation method> The blast furnace operation method of the present invention uses the amount of cohesive zone slag (CSV) as one of the operation management indicators. T ) is used. Specifically, CSV T The target value of CSV is set based on the estimation method described above.T The method for operating a blast furnace is characterized by carrying out at least one of (a) to (d) so that the estimated value of is equal to or less than the target value.

[0065] (a) Adjustment of the mixture ratio of iron-containing materials charged to the blast furnace (b) Adjusting the content of one or more of CaO, SiO2, Al2O3, MgO, CaO / SiO2, and FeO in the iron-containing charge charged to the blast furnace. (c) Adjusting the particle size of iron-containing charge fed to the blast furnace (d) Adjusting the amount of carbonaceous burden mixed into the iron-containing burden layer

[0066] Here, the CSV T The target value may be set to 920 to 980 kg / tp. As described later in Example 1, CSV T By setting the range of 920 to 980 kg / tp, the permeability of the blast furnace is significantly improved. Additionally, CSV T It is preferable to set the target value of 830 to 890 kg / tp. As described later in Example 2, CSV T By setting the range of 830 to 890 kg / tp, not only the permeability can be improved but also the reducing agent rate can be reduced. The details of the adjustments (a) to (d) will be explained below in order.

[0067] (Adjustment of the mixture ratio of iron-containing materials charged into the blast furnace) The method of adjusting the blending ratio of iron-containing charges will be explained using Table 2. The specifications of sinter A, lump ore B, and pellets C are shown in Table 1. The CSV at this time is operated with a sinter ratio of 70%, lump ore ratio of 15%, and pellet ratio of 15%. T The ventilation rate was 1035 kg / tp (operation 1). If the ventilation becomes unstable due to some reason, for example, CSV T The target value is reduced by 30 kg. To achieve this target value, for example, 10% of lump ore can be replaced with 10% sintered ore. This will reduce the CSV T will be reduced from 1035kg / tp to 1004kg / tp (Operation 2).

[0068] Furthermore, the lower K value is calculated using the correlation equation (K value = 0.0031 × CSV) obtained in Figure 3(b). T -0.9), we can expect a decline from 2.3 to 2.2.

[0069] [Table 2]

[0070] (Adjustment of chemical composition of iron-containing charge to be charged into blast furnace) A method for adjusting the chemical composition of the iron-containing charge will be explained using Table 2. The specifications of sinter B are shown in Table 1.

[0071] It is also possible to switch to Operation 3, in which sinter B having a high T.Fe content is used in place of sinter A in Operation 1. T It is expected that the lower K value will decrease from 2.3 to 2.1 (Operation 3).

[0072] (Adjustment by controlling the particle size of the charge) The reaction characteristics of blast furnace charge are determined mainly by solid-gas reactions, so they are highly dependent on particle size. T It is advisable to use CSV'' which takes into account the effect of the particle size of the charge, as described below.

[0073] Figure 5 shows the results of investigating the particle size dependence of CSV for sintered ore and lump ore. Here, the average particle size MS (mm) is the weight-based average diameter calculated from the following formula: MS = Σ(Wi Di) / ΣWi Wi Weight of grain size class i (g) Di Median of grain size class i (mm) As shown in Fig. 5, the CSV increased with an increase in the mean particle size (MS) of all iron-containing burden materials, but the influence coefficient was +28 (kg / tp) / (MS+1mm) regardless of the type of iron-containing burden material.

[0074] Using this influence coefficient, the CSV' of the iron-containing charge taking into account the particle size can be defined by equation (13). CSV'(kg / tp)=Σ(CSV''i·wi·T.Fei) / Σ(wi·T.Fei)···(13)

[0075] CSV'' i is the CSV of the iron-containing charge taking into account particle size, and can be expressed by the following formula:

[0076] CSV'' i (kg / tp)=CSV i +28×(MS-12.5) MS(mm): Average particle size of the charge (mm) Wi: Blending ratio of charge i (mass%) or blending unit (kg / tp) T.Fei: T.Fe of charge i (mass%)

[0077] Conversely, the CSV'' can be adjusted by controlling the particle size of the burden materials. Table 2 shows an example of operation 4 in which pellets C are entirely replaced with pellets C'' which have a particle size 5 mm smaller. The CSV'' of pellets C'' is 761, which is 28 x 5 = 140 smaller than the 901 of pellets C. The CSV of the burden material is 1014 kg / tp, and it is expected that the lower K value will improve from 2.3 to 2.2.

[0078] (Adjustment by mixing charcoal) Figure 6 shows the CSV measured using a load-softening test device when carbon-containing materials were mixed into a layer of pure sintered ore. Sintered ore with a particle size of 10-15 mm, lump coke with a particle size of 15-20 mm, small lump coke with a particle size of 10-15 mm, and unburned carbon-containing pellets (carbon-containing agglomerated ore) containing 20% ​​carbon were used. Although the degree varies depending on the type of carbon-containing material, the CSV decreases as the amount of mixture increases. This is the result of a carbon gasification reaction (CO generation) occurring in the mixed layer, regenerating the reduction potential of the reducing gas. Note that the finer the particle size of the carbon contained, the greater the degree of decrease in CSV.

[0079] In this case, the CSV reduction coefficient, "change in CSV (kg / tp) / (+1kg / tp)", is roughly as follows, based on Figure 6. Lump coke (particle size: 15-20mm): -1.0 Small coke (particle size: 10-15mm): -2.0 Carbon-bearing agglomerate (particle size: 10~15mm): -3.3 Therefore, the CSV value can be controlled by mixing various carbon-containing materials into the iron-containing charge. EXAMPLES

[0080] Next, an embodiment of the present invention will be described, but the conditions in the embodiment are merely an example of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to this example of conditions. Various conditions can be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.

[0081] Example 1 Sintering area is 600m 2 Sintered ores with different T.Fe contents were produced using a sintering machine. The composition conditions and firing conditions (mainly the firing heat level) were changed to change the structure of the sintered ore. The sintered ores were subjected to a load-softening test to measure the softening point reduction ratio Rs and calculate the CSV of each sintered ore.

[0082] 5000m 3 In the operation of the blast furnace, 80% of the produced sintered ore was used. The wind pressure fluctuation was kept below 43hPa, the gas utilization rate ηCO was 50.0% or more, and the molten iron temperature was 1500℃ or more.

[0083] The operational results are shown in Figure 7. Figure 7(a) shows the operational results when evaluated using the "cohesive zone slag amount" of the present invention, and Figure 7(b) shows the operational results when evaluated using the conventional "slag amount." As shown in Fig. 7(a), even if the T.Fe content is different, operation is good if sintered ore with a CSV of 950 kg / tp or less is used. Specifically, operation is possible at a low RAR without causing large fluctuations in aeration.

[0084] However, even in the case of sintered ore with a low gangue content and a T.Fe content of 60%, if the porosity is extremely low and Rs is low due to manufacturing conditions with excessive heat, the CSV will exceed 950 kg / tp, and operation will deteriorate.

[0085] On the other hand, even with sintered ore with a high gangue content and T.Fe of 54.0%, if the burden mix conditions and firing conditions are optimized and Rs is high, CSV T The operation is good, with the amount of waste being reduced to 950 kg / tp or less.

[0086] In contrast, when using the conventional indicator "slag volume," as shown in Figure 7(b), it is not possible to centrally evaluate the operation of a blast furnace that uses the above-mentioned sintered ore.

[0087] Example 2 Using sintered ore with different SiO2 contents ranging from 4.2 to 5.1 mass%, softening tests under load and BIS furnace evaluation tests were carried out. In order to simulate the improvement of coke reactivity due to alkali circulation in an actual blast furnace, the BIS test conditions were as follows: coke with alkali (3 g / charge of KOH added), reducing agent ratio 481 kg / tp, pulverized coal injection 132 kg / tp (O / C 4.63, sintered ore ratio 100%, bosh gas 1343 Nm 3 / tp.

[0088] The BIS furnace is a test method that simulates the countercurrent reaction in the shaft of a blast furnace. Sintered ore and coke are charged in layers into a pre-fixed reaction tube, and the heating electric furnace is moved from the top to the bottom of the reaction tube. The reducing gas is circulated from the top to the bottom of the reaction tube during this process, simulating the countercurrent reaction in a blast furnace. The reaction efficiency (shaft efficiency) is evaluated from the component values ​​of the obtained exhaust gas (top gas). Details of the test equipment are described in Utility Model JPU: S59-191597, and the test method is described in Non-Patent Document: Iron and Steel (1986) 1529, so they are omitted here.

[0089] The test results are shown in Figure 8. The S value (time integral value of pressure loss) in the load-softening test decreased as the CSV decreased (Figure 8b), and the shaft efficiency in the BIS test also improved (Figure 8a). In particular, sintered ore with a CSV of 860 kg / tp or less showed a high shaft efficiency of over 97% in the BIS furnace.

[0090] Example 3 A blast furnace operation test was conducted using two types of sintered ore 1 and sintered ore 2 with different CSVs shown in Table 3.

[0091] [Table 3]

[0092] The reducing agent rate of blast furnace operation during the period when sintered ore 2 was used, where the CSV was 860 kg / tp, was 5 kg lower per ton of molten iron than the reducing agent rate during the period when sintered ore 1 was used, where the CSV was 995 kg / tp.

[0093] From these results, it was found that by setting the CSV to 860 kg / tp or less, not only was the air permeability improved, but the reducing agent ratio could also be reduced. [Industrial Applicability]

[0094] As described above, according to the present invention, in blast furnace operation in which a mixture of sintered ore, pellets, lump ore, and other charges is charged, it is possible to perform an appropriate charge mix design that can improve furnace permeability, and as a result, it is possible to suppress a temperature drop in the lower part of the blast furnace and stabilize operation. Furthermore, according to the present invention, it is possible to reduce the reducing agent rate in blast furnace operation, thereby saving energy and reducing CO2.

[0095] Therefore, the present invention will make a significant contribution to industry and society, and has high industrial applicability.

Claims

1. A method for estimating a cohesive zone slag amount, which is an amount of molten liquid present on an upper surface of a cohesive zone formed by melting the iron-containing charge, in a blast furnace operation in which an iron-containing charge and a carbonaceous charge are alternately charged into the blast furnace and the iron-containing charge is heated and reduced to produce pig iron, comprising estimating a cohesive zone slag amount: CSV (kg / tp), which is an amount of molten liquid present on an upper surface of the cohesive zone formed by melting the iron-containing charge, as the sum of an amount of FeO (kg / tp) remaining on the upper surface of the cohesive zone of the iron-containing charge and an amount of gangue (kg / tp) of the iron-containing charge.

2. The method for estimating the amount of cohesive zone slag according to claim 1, characterized in that a load-softening test is performed on the iron-containing burden to determine the reduction rate Rs of the iron-containing burden when the rate of increase in pressure drop due to a temperature increase is 10 (mmAQ / ℃) or more, and the remaining FeO amount (kg / tp) is calculated by the following formula (Ix). Residual FeO amount (kg / tp) = (1833.236-202.842 x FeO [%] / T.Fe [%]) x (1-Rs / 100)... (Ix) T. Fe: Total iron content (%) in the iron-containing charge FeO: Amount of FeO in iron-containing charge (%) Rs: Reduction rate (%) at the time of pressure drop increase measured in a load-softening test on iron-containing charge

3. CSV of the entire charge consisting of multiple iron-containing charges T The method for estimating the amount of slag in the cohesive zone according to claim 1 or 2, characterized in that (kg / tp) is calculated by the following formula (II). CSV T (kg / tp)=Σ(CSV i ・w i ・T.Fe i ) / Σ(w i ・T.Fe i )・・・(II) CSV i :Slag amount of iron-containing charge i (kg / tp) W i : Mixture ratio (%) of iron-containing charge i (mixture unit (kg / tp) may be used instead of the mix ratio. However, one or the other should be used for calculation.) T.Fe i :Total iron content of iron-containing charge i (%)

4. A blast furnace operation method, comprising: determining a target value for the amount of slag in the cohesive zone; and performing at least one of (a) to (d) so that an estimated value of the amount of slag in the cohesive zone using the method for estimating the amount of slag in the cohesive zone according to any one of claims 1 to 3 is equal to or less than the target value. (a) Adjustment of the mixing ratio of iron-containing materials charged to a blast furnace (b) CaO and SiO in the iron-containing charge charged into the blast furnace 2 , Al 2 O 3 , MgO, CaO / SiO 2 and adjusting the content of one or more of FeO (c) Adjustment of particle size of iron-containing charge to be charged into blast furnace (d) Adjusting the amount of carbonaceous charge mixed into the iron-containing charge layer

5. The blast furnace operating method according to claim 4, characterized in that the target value of the cohesive zone slag amount is 920 to 980 kg / tp.

6. The blast furnace operating method according to claim 4, characterized in that the target value of the cohesive zone slag amount is 830 to 890 kg / tp.

Citation Information

Patent Citations

  • Method for judging cohesive zone formation process in blowing-in process of blast furnace

    CN104611484A

  • Estimation of shape of melt deposition zone in blast furnace

    JP1981098407A

  • Method for regulating blending of starting material containing iron for charge into blast furnace

    JP1984038308A

  • Method for controlling high-temperature characteristic of sintered ore

    JP1985089525A

  • Method for operating blast furnace

    JP1991170607A